Developing a complexity metric for inner classes - Sim, Hui Tee; Atan, Rodziah; Abdul Ghani, Abdul Azim (Asian Research Publication Network, 2010)
In some of the object-oriented programming languages such as Java, a regular class could contain one or more nested classes. These nested classes are called inner classes which are supposed to carry out more specific tasks for their outer class. However, extensive use of inner classes would result in increasing program complexity and costly maintenance. We propose a complexity metric to measure the complexity extent of inner classes. Our metric is able to measure the complexity of inner classes in term of breadth and depth. © 2005 - 2009 JATIT. All rights reserved.